2019
DOI: 10.1039/c9tc02666e
|View full text |Cite
|
Sign up to set email alerts
|

A novel cucurbit[6]uril-based supramolecular coordination assembly as a multi-responsive luminescent sensor for Fe3+, Cr2O72− and isoquinoline antibiotics in aqueous medium

Abstract: Multi-responsive cucurbit[6]uril-based coordination polymer, luminescent sensor for highly selective and sensitive detection of Fe3+, Cr2O72− and isoquinoline antibiotics in aqueous medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…These two oxo-anions are both cytotoxic and carcinogenic, and leads to the disruption of various proteins, enzymes and DNAs in the animal body. (Dong et al, 2016;Chen et al, 2017a;Dong et al, 2017;Sun et al, 2019) Thus, it is of vast significance to monitor minute presence of Fe 3+ and/or Cr(VI) ions in aqueous media via highly sensitive, fast-responsive and easily portable method. (Xu and Yan, 2015;Li et al, 2019;Singh et al, 2020) As of now, conventional procedures include high-performance liquid chromatography (HPLC), ion-exchange chromatography, gas chromatography (GC), gas chromatography-mass Spectrometry (GC/MS), ion-exchange chromatography and other detection techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two oxo-anions are both cytotoxic and carcinogenic, and leads to the disruption of various proteins, enzymes and DNAs in the animal body. (Dong et al, 2016;Chen et al, 2017a;Dong et al, 2017;Sun et al, 2019) Thus, it is of vast significance to monitor minute presence of Fe 3+ and/or Cr(VI) ions in aqueous media via highly sensitive, fast-responsive and easily portable method. (Xu and Yan, 2015;Li et al, 2019;Singh et al, 2020) As of now, conventional procedures include high-performance liquid chromatography (HPLC), ion-exchange chromatography, gas chromatography (GC), gas chromatography-mass Spectrometry (GC/MS), ion-exchange chromatography and other detection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…( Xu et al, 2016 ; Yang et al, 2019 ) In this direction, the readiness of new sensors for Fe(III) ion detection is as yet a challenging objective. ( Lustig et al, 2017 ; Sun et al, 2019 ) Alongside, chromium is also essential for mankind. Cr (III) is an essential biological element while Cr(VI) ion as CrO 4 2− and Cr 2 O 7 2− oxo-anions is employed as an oxidising agent in manufacturing processes ( Lv et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some water-stable LMOFs based on luminescent organic ligands were prepared for antibiotics detection. [62][63][64][65][66][67][68][69][70][71][72][73][74][75] For instance, a highly stable pillar-layer Znbased LMOF, [Zn 2 (TRZ) 2 (DBTDC-O 2 )]•DMAc (H 2 DBTDC-O 2 = S,S-dioxodibenzothiophen-3,7-dicarboxylic acid, HTRZ = 1,2,4triazole, and DMAc = N,N-dimethylacetamide) was prepared by using hard-soft-acid-base (HSAB) and dual-ligand strategies, which has the water stability and luminescence emission. 62 The corresponding K sv values for NFZ and NFT were 5.2 × 10 4 and 1.8 × 10 5 M −1 with the LOD of 4.04 × 10 −7 and 3.53 × 10 −7 M, respectively.…”
Section: Electronic-rich Conjugated Organic Ligand-based Lmofsmentioning
confidence: 99%
“…[19] The outer surface of the cucurbit[n]uril is composed of a large number of nitrogen atoms and carbon atoms and the cavity has a certain degree of hydrophobicity that can form a stable host-guest inclusion complex with a guest molecule via non-bonding interactions, such as hydrogen bonds, van der Waals forces and ionic dipoles. [20][21][22][23][24][25][26][27] It has been proved that cucurbit[n]urils can be used as non-toxic and safe drug carriers, [28][29][30] among which cucurbit [8]uril (Q [8]) [31] has a large cavity with certain application value in increasing the solubility, [32] stability [33] and release rate [34] of drug molecules. However, research studies on using cucurbit[n]urils as a drug carrier for chloramphenicol have not been reported to date.…”
Section: Urils (B)mentioning
confidence: 99%